Graft-Versus-Host Disease Prevention by In Vitro-Generated Myeloid-Derived Suppressor Cells Is Exclusively Mediated by the CD11b+CD11c+ MDSC Subpopulation - Scheurer, Jasmin; Kitt, Kerstin; Huber, Heinrich J.; Fundel-Clemens, Katrin; Pflanz, Stefan; Debatin, Klaus-Michael; Strauss, Gudrun (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) are a heterogenous population of myeloid progenitor cells that dampen overwhelming adaptive immune responses through multiple mechanisms and are recognized as an attractive novel immune intervention therapy for counteracting the destructive effects of Graft-Versus-Host Disease (GVHD) developing after allogeneic bone marrow transplantation (BMT). MDSCs can be produced in great numbers for cellular therapy, but they present a mixture of subsets whose functions in GVHD prevention are undefined. Here, we generated MDSCs in vitro from murine BM cells in the presence of GM-CSF and defined the integrin CD11c as a marker to subdivide MDSCs into two functional subgroups: CD11b+CD11c+ and CD11b+CD11c- MDSCs. Isolated CD11b+CD11c+ and CD11b+CD11c- MDSCs both inhibited alloantigen-stimulated T cell proliferation in vitro, although CD11b+CD11c+ MDSCs were more efficient and expressed higher levels of different immunosuppressive molecules. Likewise, expression of surface markers such as MHC class II, CD80, CD86 or PD-L1 further delineated both subsets. Most importantly, only the adoptive transfer of CD11b+CD11c+ MDSCs into a single MHC class I-disparate allogeneic BMT model prevented GVHD development and strongly decreased disease-induced mortality, while CD11b+CD11c- MDSCs were totally ineffective. Surprisingly, allogeneic T cell homing and expansion in lymphatic and GVHD target organs were not affected by co-transplanted CD11b+CD11c+ MDSCs indicating a clear contradiction between in vitro and in vivo functions of MDSCs. However, CD11b+CD11c+ MDSCs shifted immune responses towards type 2 immunity reflected by increased Th2-specific cytokine expression of allogeneic T cells. Induction of type 2 immunity was mandatory for GVHD prevention, since CD11b+CD11c+ MDSCs were ineffective if recipients were reconstituted with STAT6 deficient T cells unable to differentiate into Th2 cells. Most importantly, the beneficial Graft-Versus-Tumor (GVT) effect was maintained in the presence of CD11b+CD11c+ MDSCs since syngeneic tumor cells were efficiently eradicated. Strong differences in the transcriptomic landscape of both subpopulations underlined their functional differences. Defining CD11b+CD11c+ MDSCs as the subset of in vitro-generated MDSCs able to inhibit GVHD development might help to increase efficiency of MDSC therapy and to further delineate relevant target molecules and signaling pathways responsible for GVHD prevention.